PENINGKATAN KEMAMPUAN KOGNITIF MENGGUNAKAN MEDIA VIDEO PEMBELAJARAN PADA ANAK USIA 5-6 TAHUN DI TK ISLAMIYAH PONTIANAK TENGGARA - Ayunisa, Radhwa; Miranda, Dian; Amalia, Annisa (Universitas Tanjungpura, 2023)
The thing of this research was to explain the enhancement of cognitive capacities using learning video media in children progressed 5-6 times at TK Islamiyah Pontianak Tenggara. This study used action exploration styles with a quantitative approach. With data sources 1 schoolteacher in group B4 and 8 children used as research subjects. The focus of research is cognitive capacities. The research was conducted in II cycles conforming of 4 capabilities each cycle, that is planning, action, observation, and reflection. The research was conducted collaboratively between the experimenter and the schoolteacher of group B4. In this research, observation, interview, and documents were used to collect data. The results showed that the I cycle lesson planning was still lacking in preparing learning resources and discussion questions. In the II cycle, the preparation of learning resources improved significantly, teachers became more active in dealing with problems. Cycle I learning implementation showed that the volume and brightness settings of the projector, recording progress, and evaluation were not maximized. In cycle II, the teacher has maximized the implementation of learning. Then, if the child has not understood the material, the child asks to rewind and pause the video to understand.The results of the first cycle assessment, there were still some children who could not mention the number symbols 1 to 10, use the number symbols to count, and could not match the numbers with the number symbols. In Cycle II, children's cognitive development increased, children could perform the 3 criteria for symbolic thinking.